Factors that Affect Buying Decisions on Kopi Kenangan - Ririn Wulandari; Natassja Calista (Institute of Computer Science (IOCS), 2022)
Within three years, Kopi Kenangan managed to increase sales and increase its outlets to 324 outlets spread across 18 major cities throughout Indonesia. It is interesting to study to get answers to what factors encourage consumers to buy Kopi Kenangan. After conducting a review of previous research, the research objective is determined, namely to analyze the effect of price, promotion, brand image, and online purchases on consumer purchasing decisions. The population is consumers who have bought Kopi Kenangan in Jakarta and Bekasi. The sample Unit is 134 respondents. Data analysis using SEM with PLS program. The results showed that price, promotion, and brand image separately affected consumer purchasing decisions. The surprising finding is that online purchases do not affect purchasing decisions. The results of this study become a reference for this and other companies in increasing their sales, as well as input for the development of the theory that different marketing strategies from competitors are driving increased purchasing decisions.